System of ultrasonic non-destructive testing of carbon fiber composite defects - Xuerui Wang; Yan Zhou (Functional Materials, 2018)
In this article a non-destructive detection software system was firstly established using Lab View and MATLAB and then a test was carried out on the application of the software system in ultrasonic non-destructive detection to verify its adaptability in detection of defects of carbon fibre composite and analyze the advantages and limitations of the detection system.